PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN JASA UMROH PADA PT. PANDI KENCANA MURNI PEKANBARU - Yuliana, Illa; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted at PT. Pandi Kencana Murni Pekanbaru which is located on Pope Street No.21 Tanggerang District, Pekanbaru. The problem in this study is the sales target which has fluctuated for five years and the percentage of sales also experienced fluctuations and the reduction in the number of buyers, this is thought to be influenced by consumer purchasing decisions. The purpose of this study was to determine the effect of product quality and promotion at PT. Pandi Kencana Murni Pekanbaru. In this study the method used is quantitative descriptive using the SPSS program. The population in this study were 118 consumers. Samples were taken based on the Slovin formula method of 54 respondents and data collection methods using a questionnaire. This study aims to determine how much influence the quality of service and promos on consumer purchasing decisions. The technique used was purposive sampling, data obtained using simple regression analysis and multiple regression analysis. The results of this study indicate the Quality of Service and Promotion has a positive and significant effect on Consumer Purchasing Decisions.Â Keywords: Service Quality, Promotion and Consumer Purchasing Decisions.